EDUKASI DINI TENTANG PORNOGRAFI BAGI USIA REMAJA AWAL BAGI SISWA/I SMA PRESTASI PRIMA JAKARTA - Anggi Maringan Hasiholan; Juniati Manik; Meylin Tanga; Andreas Budi Setyobekti (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
Adolescence is a period of searching for identity and a high desire to know many things, including sexuality and pornography. Advances in technology make it easy for teenagers to access and watch pornographic content so that they become addicted. This condition hurts adolescents' brain systems and behavior, so it is necessary to provide an early understanding of viewing pornographic content wisely. The purpose of this article is to describe educational efforts for teenagers at Prestasi Prima Jakarta High School. The research method used is descriptive qualitative. Community Service activities are carried out through webinars using a google meet with the Prestasi Prima Jakarta High School students who are members of a Christian spiritual fellowship as participants. The results of this webinar provide enlightenment and understanding to teenagers, especially about the importance of knowing the effects of pornography addiction, which can damage their self-confidence, and how to deal with it when they are addicted to pornography.